2005
DOI: 10.1191/0269216305pm1050oa
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for place of care and place of death among informal caregivers of the terminally ill

Abstract: The ethic of self-control and choice for the care recipient must be balanced with consideration for the well being of the informal caregiver and responsiveness of the community service system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 20 publications
5
146
0
3
Order By: Relevance
“…Management of these symptoms represents an important target for quality improvement because shortness of breath or pain commonly prompt visits to the emergency department or admission to hospital at the end of life. [39][40][41] Our results also describe how patient characteristics are associated with particular symptom scores. Not surprisingly, comorbidity was associated with higher symptom scores.…”
Section: Sarcomamentioning
confidence: 88%
“…Management of these symptoms represents an important target for quality improvement because shortness of breath or pain commonly prompt visits to the emergency department or admission to hospital at the end of life. [39][40][41] Our results also describe how patient characteristics are associated with particular symptom scores. Not surprisingly, comorbidity was associated with higher symptom scores.…”
Section: Sarcomamentioning
confidence: 88%
“…[5][6][7] Moreover, studies suggest that patients, families, and healthcare providers believe end-of-life care should be home-based and focused on ameliorating patient symptoms rather than hospital-based and focused on extending life through invasive approaches. [23][24][25][26][27] Furthermore, high-intensity care at the end of life for advanced cancer patients may contribute to wasteful spending in the United States. [28][29][30] There are several possible explanations for our finding of less high-intensity care in the VHA at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…19 Brazil and colleagues' Canadian study of 216 bereaved family caregivers revealed 77% had a preferred place of death (two thirds preferred the home), and they reported 68% of their deceased family members also had a preferred place of death. 20 A Netherlands survey of the general public revealed their conception of a good death often required that a decision be made by the person and/or family members on the place of death and dying. 21 Another study involving 1035 U.S. psychology students found they were willing and able to talk about death place, with Caucasian Americans more positive about home deaths than African Americans.…”
Section: Literature Reviewmentioning
confidence: 99%